Effects of Split Application of Urea on Greenhouse Gas and Ammonia Emissions From a Rainfed Maize Field in Northeast China - Dong, Dan; Yang, Weichao; Sun, Hao; Kong, Shuang; Xu, Hui (Frontiers in Environmental Science, 2022)
Split application of nitrogen (N) fertilizers during different crop growth stages to fulfil the crop N requirements reduces soil mineral N concentrations and improves the efficiency of crop N fertilizer use, and can decrease nitrous oxide (N2O) emission from the soil. However, inconsistent results regarding N2O emissions have been reported in rainfed areas. Furthermore, few long-term studies have explained the effects of split N application on soil methane (CH4) flux, thus, limiting complete assessment of the effects of split N application on total greenhouse gas (GHG) emissions. Therefore, long-term monitoring is urgently required to understand the impacts of split N application on GHG emissions in rainfed areas. In this study, a six-year field experiment was conducted in a rainfed maize (Zea mays L.) field in Northeast China. The experiment included three treatments: no N application representing control (CK), single application at sowing stage of maize (SU), and split N at the sowing and jointing stages at a ratio of 1 : 2 (SF). Between the sowing and jointing stages, N2O emissions were significantly higher in SU than in SF. However, high N2O emissions were observed in SF for one month after N application at the jointing stage possibly because the time of N application coincided with optimum precipitation and soil temperature conditions, which stimulated N2O emissions. Overall, the total N2O emissions showed no significant difference between SU and SF. During the study period, split application of N fertilizer did not significantly affect the cumulative CH4 flux. Compared to CK, the yield-scaled GWP in SF treatment increased by 18.7% (p < 0.05). Ammonia (NH3) volatilization in SF was 272% higher than that in SU. The findings indicated that split N application exhibited an environmental risk by increasing yield-scaled GWP and NH3 emissions in the field. Thus, this study suggested that single N application applied in sowing stage should be employed in rainfed fields to mitigate yield-scaled GWP and NH3 emissions and maintain efficient maize yields.